LANGUAGE IDENTITY AND THE ROLE OF THE SOCIAL FACTOR IN ITS FORMATION - Umurzakova, Markhabo (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
The concept of linguistic identity is multifaceted, as it is the object of pragmalinguistics, psycholinguistics, sociolinguistics, cognitive linguistics, and linguocultural studies. Each language speaker, as a separate person, shows the possibilities of using the language in his/her own way. Various factors influence their acquisition of language skills, particularly social factors also play a role. The article deals with the question of the role of the family in the manifestation of the language identity. As much as the role of the family is important in the formation of a person, the environment in the family is also considered to be essential in the formation of a person as a language identity. Cultural traditions of the community to which the family belongs, moral environment, religious affiliation, place of residence, parent's language identity, parent's occupation, etc. are considered important in the formation of the language identity. The article focuses on the issue of the influence of the family on the manifestation of the language identity.
Keywords: linguopersonology; linguistic personality; social factor; types of linguistic personality; linguistic portrait; thinking; culture; social position; discourse